DC Transport and Magnetotransport Properties of the 2D Isotropic Metallic System with the Fermi Surface Reconstructed by the Charge Density Wave - Barbara Keran; Petra Grozić; Anatoly M. Kadigrobov; Zoran Rukelj; Danko Radić (Condensed Matter, 2022)
We report the ground state stabilization and corresponding electrical transport and magnetotransport properties of a 2D metallic system with an isotropic Fermi surface reconstructed by a charge density wave. The onset of the charge density wave is a spontaneous process, stabilized by the condensation energy gain due to the self-consistent mechanism of topological reconstruction of the Fermi surface and opening of the pseudo-gap around it. We address the signature of the uni-axial reconstruction in terms of the measurable quantities, such as the intra-band transport properties, including the one-particle density of states, the total and effective concentration of electrons, and the Hall coefficient. Additionally, we analyze the magnetotransport properties of the system reconstructed by the bi-axial, checkerboard-like charge density wave, under conditions of magnetic breakdown. It manifests huge quantum oscillations in diagonal components of magnetoconductivity, while the Hall conductivity changes sign, varying the external magnetic field with a finite region of vanishing Hall coefficient in between.